Rozwiązanie:
[tex]cos(\pi +\alpha )=\frac{5}{13}\\sin(6\pi +\alpha )>0[/tex]
Stąd wynika, że:
[tex]cos(\pi +\alpha )=-cos\alpha =\frac{5}{13} \Rightarrow cos\alpha =-\frac{5}{13}\\sin(6\pi +\alpha )=sin\alpha >0[/tex]
Zatem [tex]\alpha \in (0,\frac{\pi }{2})[/tex], co oznacza, że [tex]tg\alpha <0[/tex]. Obliczamy [tex]tg\alpha[/tex] :
Z jedynki trygonometrycznej:
[tex]sin^{2}\alpha =1-cos^{2}\alpha =1-\frac{25}{169} =\frac{144}{169}\\sin\alpha =\frac{12}{13}[/tex]
Zatem:
[tex]tg\alpha =\frac{sin\alpha }{cos\alpha }=\frac{12}{13}*(-\frac{13}{5})=-\frac{12}{5}[/tex]